Command transitions in public administration : a quantitative and qualitative analysis of proactive strategies /: a quantitative and qualitative analysis of proactive strategies. ([2016]) - Brown, James C; Philo, Raymond L; Callisto., Anthony; Smith, Polly J
No abstract available